Small‐scale fisheries and local food systems: Transformations, threats and opportunities - Arthur, Robert I; Skerritt, Daniel J; Schuhbauer, Anna; Ebrahim, Naazia; Friend, Richard M; Sumaila, U Rashid (Fish and fisheries (Oxford, England), 2022)
Fish from marine and inland capture fisheries is an important food that contributes significantly to diets and health, but their contribution is somewhat overlooked in food security and poverty‐related policies. Given the current numbers of malnourished people globally, there is a pressing need to consider how to better realize the potential of fish in food systems that can address malnourishment. To do so, we re‐examine the fisheries literature from the perspective of food systems. Starting with nutritional needs and considering how these may be met through local food systems reveals an ongoing transformation that has implications for small‐scale fisheries, as increasingly become part of globalized food systems. We describe the factors that can change the nature of production, mediate access to fish and the distribution of benefits that can lead to impoverishment. This emphasizes the governance challenges that lie at the heart of complex, contested and increasingly globalized food systems, in which actors interact to shape the systems, determining who benefits and how. We draw attention to critical issues of access, power and the values and norms that underpin efforts to manage and transform fisheries, exposing the unequal struggle to secure access that small‐scale fishers and poor people must endure. We suggest a vital challenge for fisheries management is to engage with this struggle and develop policies and management measures that would enable fisheries to make positive contributions to food systems and nutritional security, while meeting global sustainable development objectives.